Novel biopolymer matrices for microencapsulation of phages: enhanced protection against acidity and protease activity - Dini, Cecilia (2012)
Phage therapy by oral administration requires enhanced resistance of phages to the harsh gastric conditions. The aim of this work is the microencapsulation of phages in natural biopolymeric matrices as a protective barrier against the gastric environment. Alginate and pectin are used as base polymers. Further emulsification with oleic acid or coating with a different biopolymer is also studied. Emulsified pectin shows the maximum encapsulation efficiency and the highest protection against acidity, leaving more than 10³ active phages after 30 min exposure at pH¼1.6, and protects phage from pepsin activity (4.2mgmL⁻¹). Non-encapsulated phages are fully inactivated at pH¼1.6 or with pepsin (0.5mgmL⁻¹) after 10 min.